A chromatin link to caste identity in the carpenter ant Camponotus floridanus - Simola, Daniel F; Ye, Chaoyang; Mutti, Navdeep S; Dolezal, Kelly; Bonasio, Roberto; Liebig, Juergen; Reinberg, Danny; Berger, Shelley L (Genome Research, 2012)
In many ant species, sibling larvae follow alternative ontogenetic trajectories that generate striking variation in morphology and behavior among adults. These organism-level outcomes are often determined by environmental rather than genetic factors. Therefore, epigenetic mechanisms may mediate the expression of adult polyphenisms. We produced the first genome-wide maps of chromatin structure in a eusocial insect and found that gene-proximal changes in histone modifications, notably H3K27 acetylation, discriminate two female worker and male castes in Camponotus floridanus ants and partially explain differential gene expression between castes. Genes showing coordinated changes in H3K27ac and RNA implicate muscle development, neuronal regulation, and sensory responses in modulating caste identity. Binding sites of the acetyltransferase CBP harbor the greatest caste variation in H3K27ac, are enriched with motifs for conserved transcription factors, and show evolutionary expansion near developmental and neuronal genes. These results suggest that environmental effects on caste identity may be mediated by differential recruitment of CBP to chromatin. We propose that epigenetic mechanisms that modify chromatin structure may help orchestrate the generation and maintenance of polyphenic caste morphology and social behavior in ants.